Dimension spectra for flows: Future and past. (June 2022) - Barreira, Luis; Holanda, Carllos
Abstract: We establish a conditional variational principle for the dimension spectrum obtained from almost additive families for a flow on a conformal locally maximal hyperbolic set, simultaneously into the future and into the past.